A Hydrogel Ionic Circuit Based High‐Intensity Iontophoresis Device for Intraocular Macromolecule and Nanoparticle Delivery. Issue 5 (8th December 2021) - Zhao, Fan; Fan, Shan; Ghate, Deepta; Romanova, Svetlana; Bronich, Tatiana K.; Zhao, Siwei
Abstract: Iontophoresis is an electrical‐current‐based, noninvasive drug‐delivery technology, which is particularly suitable for intraocular drug delivery. Current ocular iontophoresis devices use low current intensities that significantly limit macromolecule and nanoparticle (NP) delivery efficiency. Increasing current intensity leads to ocular tissue damage. Here, an iontophoresis device based on a hydrogel ionic circuit (HIC), for high‐efficiency intraocular macromolecule and NP delivery, is described. The HIC‐based device is capable of minimizing Joule heating, effectively buffering electrochemical (EC) reaction‐generated pH changes, and absorbing electrode overpotential‐induced heating. As a result, the device allows safe application of high current intensities (up to 87 mA cm −2, more than 10 times higher than current ocular iontophoresis devices) to the eye with minimal ocular cell death and tissue damage. The high‐intensity iontophoresis significantly enhances macromolecule and NP delivery to both the anterior and posterior segments by up to 300 times compared to the conventional iontophoresis. Therapeutically effective concentrations of bevacizumab and dexamethasone are delivered to target tissue compartments within 10–20 min of iontophoresis application. This study highlights the significant safety enhancement enabled by an HIC‐based device design and the potential of the device to deliver therapeutic doses of macromolecule and NP ophthalmic drugs within a clinically relevant time frame. Abstract : An iontophoresis device based on a hydrogel ionic circuit (HIC) is developed for highly effective intraocular delivery of macromolecule and nanoparticle drugs. The HIC‐based device allows safe application of high current intensities (up to 87 mA cm −2 ) to the ocular tissue. Moreover, therapeutically effective concentrations of bevacizumab and dexamethasone in a nanoparticle formulation can be delivered to target tissues within 10–20 min of iontophoresis application.